Analysis of Supplier Selection of Steel Plate Raw Materials on Railways using Analytical Hierarchy Process (AHP) and Additive Ratio Assessment (ARAS) Methods at PT XYZ - -, Dira Ernawati; Tranggono; Yekti Condro Winursito (Program Studi Teknik Industri S-1, Fakultas Teknik UPN Veteran Jakarta, 2025)
Companies need to develop a good business strategy in order to compete, including in choosing quality raw materials from the best suppliers. This research aims to select the best steel plate raw material supplier at company XYZ by using the Analytical Hierarchy Process (AHP) and Additive Ratio Assessment (ARAS) methods. This research involves the process of primary and secondary data collection which includes identifying supplier selection criteria, collecting data for each criterion, and collecting performance data from suppliers. The results showed that the order of the best steel plate raw material suppliers at company XYZ with the largest value was ranked 1st supplier company Steel Kras with a K value of 0,195207; ranked 2nd supplier company Jaraindo with a K value of 0,137696; ranked 3rd supplier company Capris with a K value of 0,135158; ranked 4th supplier company Kamaseta with a K value of 0,116481; ranked 5th supplier company Wima Indo with a K value of 0,106039 and ranked 6th supplier company Cenia Mandiri with a K value of 0,084586. Based on the AHP and ARAS methods, the relative weight of each criterion has been calculated, which helps in evaluating the best or potential suppliers to choose from. In addition, the ranking of suppliers is also determined based on the resulting priority value.